2009
DOI: 10.1038/ajh.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Adaptation in Pregnant Hypertensive Rats: Improvement of Vascular and Inflammatory Variables and Oxidative Damage in the Kidney

Abstract: The increased proinflammatory and oxidative variables, seen in SHR, are strongly ameliorated by pregnancy. In pregnant SHR animals, the adaptive and compensative changes of RAS and inflammation in the kidney seem to contribute to the reduction of blood pressure near term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…There is recent evidence that the increased proinflammatory and oxidative markers (malondialdehyde content and protein nitrosylation) seen in SHRs are greatly ameliorated by pregnancy. 16 Together with changes in the renin-angiotensin system in the kidney, reduction of oxidative markers seems to contribute to the reduction of blood pressure near term in SHRs, as observed in our study. Future studies on oxidative stress in pregnant SHRs should be carried out in other tissues and platelets to support the hypothesis that a decrease in oxidative stress near term may contribute to the maintenance of NO and cGMP bioavailability.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…There is recent evidence that the increased proinflammatory and oxidative markers (malondialdehyde content and protein nitrosylation) seen in SHRs are greatly ameliorated by pregnancy. 16 Together with changes in the renin-angiotensin system in the kidney, reduction of oxidative markers seems to contribute to the reduction of blood pressure near term in SHRs, as observed in our study. Future studies on oxidative stress in pregnant SHRs should be carried out in other tissues and platelets to support the hypothesis that a decrease in oxidative stress near term may contribute to the maintenance of NO and cGMP bioavailability.…”
Section: Discussionsupporting
confidence: 67%
“…The levels obtained from pregnant hypertensive rats were not significantly different from those obtained from the normotensive groups, which were in agreement with previous findings. 15,16,21 These results might be partially explained by an increased production of NO and prostacyclin from vascular endothelium 20 and a hyporeactivity to vasoconstrictors, 34 which may contribute to vasodilation and consequent reduction in peripheral vascular resistance. Although a specific role for NO in the induction of hemodynamic alterations in pregnancy is somewhat controversial, it is widely accepted that an excess of NO is generated by endothelial cells during normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we observed that the Dahl S rat does exhibit worsening hypertension in late pregnancy, in contrast to both the normotensive SD and the hypertensive SHR. Healthy pregnancy is characterized by a decrease in systemic vascular resistance and blood pressure, likely due to increased nitric oxide-mediated vasodilation (40), and this typical response is observed in both the SD and SHR (4,15,19,37). However, the Dahl S rat exhibits a slight but significant increase in MAP, resulting in a ϳ20 mmHg difference in pressure compared with the expected drop that should occur at late pregnancy.…”
Section: R65mentioning
confidence: 99%
“…Hypertension in the spontaneously hypertensive rat is ameliorated during pregnancy, an effect that is associated with a reduction in the renal AT 1 R:AT 2 R ratio and decreased inflammation as indicated by downregulation of nuclear factor-κB in the kidney. 30 Collectively these findings suggest that the AT 2 R suppresses AT 1 R-mediated immune system activation within the kidney during pregnancy. Because the increase in the renal Th1:Th2 ratio preceded the rise in arterial pressure during late gestation in AT 2 R-KO mice, this suggests that renal inflammation may contribute to pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 79%